Perspektywy zmian w przestrzeni społeczno-ekonomicznej Dolnego Śląska - Korenik, Stanisław (The Prospects of Changes in Social and Economic Space of Lower Silesia, 2006)
Nowadays changes of values in many fields of economic life concern among others the changes in spatial elements that are regions. Observing the changes in Lower Silesia economy we can point out the growing disproportion due to the forming of Wrocław Metropolitan Area on the one hand and the raising specialization of particular spatial elements on the other hand. The present and predicted changes will cause that the region will become more and more modern and high-developed area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 141-157